A bicyclic pentapeptide-based highly potent and selective pan-SIRT1/2/3 inhibitor harboring Nε-thioacetyl-lysine. Issue 7 (1st April 2020) - Li, Renwu; Yan, Lingling; Sun, Xun; Zheng, Weiping
Graphical abstract: Bicyclic pentapeptide 10 harboring the catalytic mechanism-based SIRT1/2/3 inhibitory warhead N ε -thioacetyl-lysine at its central position was found to be a highly potent/selective ( versus SIRT5/6/7), proteolytically stable, and cell permeable pan-SIRT1/2/3 inhibitor which also exhibited an anti-proliferative effect on the human SK-MEL-2 melanoma cells. Abstract: Past few years have seen an active pursuit of the inhibitors for the deacylation catalyzed by the seven human sirtuins (i.e. SIRT1-7) as valuable chemical biological/pharmacological probes of this enzymatic deacylation and lead compounds for developing novel therapeutics for human diseases. In the current study, we prepared eight monocyclic and one bicyclic analogs of a linear pentapeptide-based potent (sub-μM IC50 's) pan-SIRT1/2/3 inhibitor Zheng laboratory discovered recently that harbors the catalytic mechanism-based SIRT1/2/3 inhibitory warhead N ε -thioacetyl-lysine at its central position. We found that the bicyclic analog exhibited largely comparable SIRT1/2/3 inhibitory potencies to those of the parent linear pentapeptide, however, the former is proteolytically much more stable than the latter. Moreover, the bicyclic analog displayed very weak inhibition against SIRT5/6/7, was cell permeable, and exhibited an anti-proliferative effect on the human SK-MEL-2 melanoma cells. This bicyclic analog could be a lead for the future development of more potent and still selective pan-SIRT1/2/3 inhibitors whose use in studies on human sirtuin biology, pharmacology, and medicinal chemistry could complement with the use of the potent inhibitors selective for a single human sirtuin.